THE USE OF CARTOON MOVIE AS A MEDIA IN TEACHING VOCABULARY TO YOUNG LEARNERS - Desi Pitriana; Jufri Syahrudin (Universitas Negeri Padang, 2013)
The media is one facilitate to teach the lesson by the teacher to the student. Media also aims to make the learning process more interesting for students. In this article, the use of cartoon movie in English language particular vocabulary is one of the alternative ways of several methods used in teaching vocabulary to students. This article also aims to enhance the student's motivation to learn English so they do not feel bored and monotonous in the study. This article can provide the English teacher in varying the media by using cartoon movies so that students are not only interested but also gain new experiences and knowledge that they can take from the lesson. By using cartoon movie, the process of learning will be fun with an atmosphere that is not monotonous and feel better than ever. Therefore, to support continuation of the learning process and attract the attention of students to learn actively and understand the lessons more easily, then use a media is recommended in the learning process. Media adalah salah satu alat untuk mempermudah penyampaian pembelajaran oleh guru kepada siswa. Media juga bertujuan untuk membuat proses belajar mengajar lebih menarik bagi siswa. Dalam artikel ini ini, penggunaan film cartoondalam pengajaran Bahasa Inggris khususnya kosa kata (vocabulary) adalah salah satu cara alternative dari beberapa metode yang dipakai dalam pengajaran kosa kata kepada siswa. Artikel ini juga bertujuan untuk meningkatkan motivasi siswa dalam belajar bahasa Inggris sehingga mereka tidak merasa bosan dan monoton dalam mempelajarinya. Artikel ini dapat memberikan masukan kepada guru bahasa Inggris dalam memvariasikan media pembelajaran dengan menggunakan film cartoon sehingga siswa tidak hanya tertarik tetapi juga memperoleh pengalaman dan pengetahuan yang baru yang dapat mereka ambil dari pelajaran tersebut. Dengan menggunakan film, proses belajar akan menyenangkan dengan suasana yang tidak monoton dan merasakan suasana belajar yang lebih baik dari sebelumnya. Oleh karena itu, untuk menunjang kelangsungan proses belajar mengajar dan menarik perhatian siswa untuk belajar aktif dan memahami pelajaran lebih mudah, maka penggunaan suatu media sangat dianjurkan sekali dalam proses pembelajaran. Kata kunci: cartoon movie, vocabulary, motivation, young learners